1986
DOI: 10.1177/01454455860103005
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mealtime Behaviors Through Token Reinforcement

Abstract: In the present study the effectiveness of a token reinforcement program in improving mealtime behaviors of four mentally retarded, behaviorally disordered children was evaluated using the multiple baseline design across behaviors. Participants were residents on an inpatient psychiatric hospital program for children. Target behaviors included appropriate utensil use, appropriate napkin use, chewing with mouth closed, and good posture. Training was implemented in a group setting and consisted of verbal instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Intervention integrity. Only two of the eight studies (Sisson & Dixon, 1986;Taylor, 2020) collected data on the integrity of the chewing intervention (see Table 3). While Sisson and Dixon (1986) reported a portion of sessions were scored for treatment integrity purposes, the integrity checklist involved just indicating if the feeder provided attention for appropriate behaviors exhibited by the participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intervention integrity. Only two of the eight studies (Sisson & Dixon, 1986;Taylor, 2020) collected data on the integrity of the chewing intervention (see Table 3). While Sisson and Dixon (1986) reported a portion of sessions were scored for treatment integrity purposes, the integrity checklist involved just indicating if the feeder provided attention for appropriate behaviors exhibited by the participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies except Volkert et al (2013Volkert et al ( , 2014, and Kadey et al (2013) examined generalization of chewing behaviors across settings or foods (see Table 3). For example, Sisson and Dixon (1986) presented data collected during probes in a natural mealtime setting and observed (2020) conducted probes during which parents presented with three foods with varying textures. One of the five studies examining generalization did not provide the data (Eckman et al, 2008), but reported generalization of chewing behaviors occurred from home to school.…”
Section: Generalization and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…Typically, attention from an adult caregiver is the most common method of reinforcement, as attention is easily delivered and highly sought after by children. For older children, the use of tangible reinforcement such as a sticker chart or point system in which points can be accumulated to earn prizes or privileges may be more motivating [40]. For these techniques to be effective, the reward must be motivating enough to change feeding behavior, and the caregivers and the child must understand and follow the reinforcement schedule.…”
Section: Behavioral Treatmentmentioning
confidence: 99%